Improvement on the mechanical properties of cork composites using suberin as coupling agent through a reactive extrusion process - Fernandes, E. M. (2011)
New functionalized composite structures were prepared using low-density polyethylene (LDPE), cork powder and different suberins extracted from cork and birch outer bark as coupling agents to promote interfacial adhesion. The compounding was performed under reactive extrusion and samples processed by compression moulding. The morphology of the functionalized composites showed good adhesion between cork and the polymeric phase. The mechanical results confirm that the addition of suberin acts as coupling agent improving the strength and leads to cork-polymer composite materials with improved strain and lower modulus. When the suberin was added to the composition a slight increase on the composite density occurred. The new cork-polymer composites demonstrated that this technological approach is industrially appealing.